PENGARUH SENAM HIPERTENSI TERHADAP PENURUNAN TEKANAN DARAH LANSIA - Minduri, Cinta; Ariyanti, Sri; Kawuryan, Uji (Jurnal Riset Keperawatan dan Kesehatan, 2025)
Background: Hypertension is one of the most prevalent non-communicable diseases among the elderly and is a major risk factor for cardiovascular complications. One non-pharmacological effort to control blood pressure is engaging in physical activity such as hypertension exercise, which is specifically designed to help lower blood pressure and improve heart health in the elderly. Objective: To determine the effect of hypertension exercise on reducing blood pressure in elderly patients with hypertension at UPT Puskesmas Gang Sehat, Pontianak City. Methods: This study employed a quasi-experimental design without a control group, using a pretest–posttest approach. The sample consisted of 17 elderly individuals selected using a Insidental sampling technique. The intervention involved performing hypertension exercise four times over two weeks, with each session lasting 20–30 minutes. Blood pressure was measured before and after the intervention. Data were analyzed using the Wilcoxon test. Results: After the intervention, the majority of respondents experienced a reduction in blood pressure. For systolic blood pressure, 13 respondents showed a decrease after performing hypertension exercise, with the Wilcoxon test yielding a significance value of p = 0.003 (p < 0.05), indicating a significant difference between systolic blood pressure before and after the intervention. For diastolic blood pressure, 12 respondents experienced a decrease, with a significance value of p = 0.028 (p < 0.05). Conclusion: Hypertension exercise is proven to be effective in lowering blood pressure in elderly patients with hypertension.